"We believe, we feel, we act": Testing the BIAS Map predictions during adolescence. Issue 1 (6th November 2019) - Constantin, Andreea A.; Cuadrado, Isabel
Abstract: The present study examined the relation between adolescents' beliefs, emotions, and intentional behaviors toward two immigrant groups from the Spanish context: Moroccans and Ecuadorians. For this purpose, we tested the SCM/BIAS Map predictions considering the three‐dimensional perspective of stereotype content, which distinguishes between morality, sociability, and competence. Spanish adolescents ( N  = 231, Mage  =  15.39, SD =  1.09) evaluated either Moroccans ( n  = 114, 55.3% girls) or Ecuadorians ( n =  117, 59% girls) on the SCM/BIAS Map variables. Our results confirmed, for both groups, the validity of the three‐dimensional model of stereotype content and showed that adolescents differentiate between the two subdimensions of warmth and treat them as independent in intergroup evaluations. Furthermore, the mediating role of emotions in the stereotype content‐behavior link was also confirmed but only for the univalent emotions in both groups. Finally, only morality acted as a consistent predictor of adolescents active behavioral intentions. The higher perceived morality of the immigrants increased adolescents' admiration toward them, which in turn led adolescents to manifest more active facilitation intentions. Likewise, the perceived morality of the immigrants negatively affected adolescents' contempt toward them, which in turn decreased adolescent's active harm intentions toward Ecuadorians and Moroccans. These findings indicate that the perceived morality of the outgroup is the key aspect in order to simultaneously promote helping behavior and decrease harmful one toward immigrant groups during adolescence.